The crop commercialization impact of cluster farming initiative in Northwestern Ethiopia - Getachew Eshetu Gidelew; Getachew Eshetu Gidelew; Bamlaku Alamirew Alemu; Koyachew Enkuahone Kassie (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn Ethiopia and other developing countries, the commercialization of smallholder agriculture is a key strategy for achieving agricultural and overall economic growth. Crop cluster farming has emerged as a growing trend in Ethiopia to support these commercialization efforts. This study assesses the impact of cluster farming on crop commercialization among smallholder farmers in Northwestern Ethiopia. It offers novel insights by considering the commercialization of both cluster and non-cluster crops, highlighting potential spillover benefits of cluster farming practices on non-target commodities—an area often overlooked in prior research.MethodsThis study used a cross-sectional research design. Data were gathered from 421 farming households through face-to-face interviews. The data was analyzed using Endogenous Switching Regression and inferential statistics, including t-tests and chi-square tests. Commercialization was measured using two indicators: the total value of crops sold and the proportion of crops sold.ResultsThe results showed that, on average, participating households earned 1,106 USD annually from crop sales, while non-participating households earned 731 USD. Additionally, participant households sold on average 50% of the crops they produced, compared to 36% for non-participants. Similarly, households engaged in cluster farming of wheat, maize, and teff reported higher incomes and proportion of sales than those who did not engage.ConclusionOur findings suggest that there is a positive association between cluster farming participation and commercialization in both indices. Thus, the scaling up of cluster farming to a wider farming community is recommended to enhance the commercialization of smallholder farmers.